Laser-driven resonance of dye-doped oil-coated microbubbles: A theoretical and numerical study - Lajoinie, G; Linnartz, E; Kruizinga, P; de Jong, N; Stride, E; van Soest, G; Versluis, M (Acoustical Society of America, 2017)
Microbubbles are used to enhance the contrast in ultrasound imaging. When coated with an optically absorbing material, these bubbles can also provide contrast in photoacoustic imaging. This multimodal aspect is of pronounced interest to the field of medical imaging. The aim of this paper is to provide a theoretical framework to describe the physical phenomena underlying the photoacoustic response. This article presents a model for a spherical gas microbubble suspended in an aqueous environment and coated with an oil layer containing an optically absorbing dye. The model includes heat transfer between the gas core and the surrounding liquids. This framework is suitable for the investigation of both continuous wave and pulsed laser excitation. This work utilizes a combination of finite difference simulations and numerical integration to determine the dependancy on the physical properties, including composition and thickness of the oil layer on the microbubble response. A normalization scheme for a linearized version of the model was derived to facilitate comparison with experimental measurements. The results show that viscosity and thickness of the oil layer determine whether or not microbubble resonance can be excited. This work also examines the use of non-sinusoidal excitation to promote harmonic imaging techniques to further improve the imaging sensitivity.